Ein Liber cantus aus dem Veneto (um 1440) - A Veneto Liber cantus (c. 1440) Fragmente in der Bayerischen Staatsbibliothek München und der Österreichischen Nationalbibliothek Wien - Fragments in the Bayerische Staatsbibliothek Munich and the Österreichische Nationalbibliothek, Vienna - Bent, Margaret; Klugseder, Robert (Reichert Verlag, 2012)
This book results from Robert Klugseder's discovery of new fragments in Vienna (Fragm. 661) and Margaret Bent's recognition that they belonged to the same original manuscript as a set of fragments in Munich (Mus. Ms. 3224, Aalready known). Together they make a torso of 12 leaves with 20 compositions, nearly half of which are unique, an important complement to the already-known Veneto manuscripts of international repertory of the first half of the 15th century. A high-quality colour facsimile of these leaves, together with associated fragmentary survivals, is preceded by an in-depth codicological and repertorial study in German and English.